Influence of seed moisture content and storage period on germination and biochemical indices: Lallemantia iberica and Lallemantia royleana - Saeideh Maleki Farahani; Alireza Rezazadeh; Arezoo Paravar (Scientific Reports)
Abstract The longevity of seeds varies greatly between species and seed viability reduction due to seed ageing is one of the major problems affecting agricultural productivity. To comprehend the mechanisms involved in the ageing, seeds of two plant species dragon head (Lallemantia iberica) and lady’s mantle (Lallemantia royleana) and with 5, 15 and 25% seed moisture content were tested for 24 and 48 h storage period at 40 °C. Increased seed moisture content and storage period significantly reduced germination percentage, protein content, catalase and ascorbate peroxidase enzyme activity. During storage, most significant deterioration was observed in L. iberica seeds showing lower germination percentage, protein content, catalase and ascorbate peroxidase enzyme activities. As a result, the cell membrane of L. iberica seeds was damaged, resulting in an increase in electrical conductivity, hydrogen peroxidase and malondialdehyde contents compared to L. royleana. Overall, the lowest deterioration was obtained in stored seeds of both Lallemantia species by 5% seed moisture content and 24 h storage period; in contrast increasing of seed moisture content and storage period induced the faster deterioration of Lallemantia seeds. Furthermore, L. iberica deteriorates rapidly by rising of seed moisture content and storage period in comparison with L .royleana.